PENERAPAN PERATURAN KEJAKSAAN REPUBLIK INDONESIA NOMOR 15 TAHUN 2020 TENTANG PENGHENTIAN PENUNTUTAN BERDASARKAN KEADILAN RESTORATIF (STUDI KASUS PADA KEJAKSAAN NEGERI DAIRI) - Alofsen Sianturi (Jurnal Perspektif Hukum, 2022)
The Republic of Indonesia Prosecutor's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice has the potential to conflict with the laws and regulations above, namely the Criminal Procedure Code and Law Number 16 of 2004 concerning the Prosecutor's Office as amended by Law Number 11 of 2021. This research uses a normative legal research type that is descriptive analytical with a statutory approach and a case approach. The results of this study indicate that the position of the Prosecutor's Office of the Republic of Indonesia Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice in the hierarchy of laws and regulations is another statutory regulation as outlined in Article 8 paragraph (1) of Law Number 12 of 2011 concerning the Establishment of Legislation. The application of the Republic of Indonesia Prosecutor's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice by the Dairi District Attorney in stopping the prosecution of criminal cases with the suspect Ucok Lumban Gaol has met the formal and material requirements. Meanwhile, the application of the Republic of Indonesia Prosecutor's Regulation Number 15 of 2020 concerning Termination of Prosecution by the Dairi District Attorney in a criminal case with the suspect Desi Megawati Sihombing does not meet the material requirements as specified in the Attorney General's Letter Number B-4301/E/EJP/9/2020 dated September 16, 2020 because Desi Megawati Sihombing's actions were seen as concurrent acts as stated in Article 65 of the Criminal Code.